2021
DOI: 10.1136/bmjopen-2020-041795
|View full text |Cite
|
Sign up to set email alerts
|

Electronic clinical decision support tool for assessing stomach symptoms in primary care (ECASS): a feasibility study

Abstract: ObjectiveTo determine the feasibility of a definitive trial in primary care of electronic clinical decision support (eCDS) for possible oesophago-gastric (O-G) cancer.Design and settingFeasibility study in 42 general practices in two regions of England, cluster randomised controlled trial design without blinding, nested qualitative and health economic evaluation.ParticipantsPatients aged 55 years or older, presenting to their general practitioner (GP) with symptoms associated with O-G cancer. 530 patients (mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 25 publications
1
14
0
4
Order By: Relevance
“…While QI tools for cancer diagnosis in primary care are posited to improve the quality of care for patients, reduce practitioner errors, and allow for efficiency in everyday practice, previous studies have reported a range of barriers to implementation and low acceptance in practice. Issues with CDSSs for cancer include tools that are underused [39], too complex [40], incompatible with the workflow [41], incompatible with GP software [42], or do not align with practitioner practice [43]. The results of this study align with the findings of a previous systematic review [28].…”
Section: Comparison With Prior Worksupporting
confidence: 65%
See 1 more Smart Citation
“…While QI tools for cancer diagnosis in primary care are posited to improve the quality of care for patients, reduce practitioner errors, and allow for efficiency in everyday practice, previous studies have reported a range of barriers to implementation and low acceptance in practice. Issues with CDSSs for cancer include tools that are underused [39], too complex [40], incompatible with the workflow [41], incompatible with GP software [42], or do not align with practitioner practice [43]. The results of this study align with the findings of a previous systematic review [28].…”
Section: Comparison With Prior Worksupporting
confidence: 65%
“…The ability to verify the recommendations by understanding the research underpinning the recommendation was not being met as part of FHT [28]. For the diagnosis of cancer, embedding tools in the workflow is often a key barrier [39]; however, the limited disruption caused by the tool and the timing of the prompt meant that FHT aligned with most participants workflow.…”
Section: Comparison With Prior Workmentioning
confidence: 99%
“…Among the 36 studies that indicated a perceived increase in consultation duration, the most commonly highlighted concerns related to existing time pressures and lack of time during a consultation for clinicians to interact with eCDS tools and/or to carry out resultant recommended actions. 16,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] A prevalent view was that workload was 'already heavy' and that using eCDS tools would inevitably add burden. 36,38,39,[41][42][43][44][45][46][47][48] In the case of one tool to support delivery of preventive care through review of patients' lifestyle factors, the sense of lack of time for preventive care in general drove the view towards the tool increasing consultation duration.…”
Section: Perceived Increase In Consultation Durationmentioning
confidence: 99%
“…49 The usual ow of tasks to complete during a consultation (often referred to as 'work ow' 31,[50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] ) was commonly expected to be disrupted by eCDS tools, causing an increase in consultation duration. 28,31,33,36,50,[65][66][67] Speci c time-consuming functions of tools, such as reading text, additional data-entry and using tools which were stand-alone from the EMR 16,36,41,46,65,[68][69][70] , as well as perceptions of poor-or slow-functioning software 45,50,67,71 were also highlighted. A potential for negative impact of eCDS tools on the trajectory of the conversation with patients was expressed by some health professionals.…”
Section: Perceived Increase In Consultation Durationmentioning
confidence: 99%
See 1 more Smart Citation